Agglomeration of knowledge in the German regional economy - Astrid Krenz (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
This article investigates the geographical location of workers in jobs with high-knowledge requirements in the German economy. Our analysis takes individual-level data from the German socioeconomic panel (GSOEP) and combines them with the knowledge information for different jobs that comes from the US Department of Labor. We make use of the regional information inherent to the GSOEP that can be accessed only through a special user contract. High-knowledge employment is differently distributed across the German regions. Whereas highknowledge employment in communication and media as well as public safety is rather concentrated across regions, high-knowledge employment in computers and electronics, engineering and technology, education and training and mechanical tasks is more dispersed. Eastern German regions display a lower share of highknowledge workers in computers, engineering, mechanical tasks and public safety. The results are important to understand the regional development potential across the German regions. Our analysis detects a division in high-knowledge employment between the East and West of Germany.
Keywords: R11; R12; J24; 330; agglomeration; knowledge; Germany